A Triazine‐Based Analogue of Graphyne: Scalable Synthesis and Applications in Photocatalytic Dye Degradation and Bacterial Inactivation. Issue 10 (3rd February 2020) - Chen, Tao; Li, Wen‐Qian; Chen, Xiao‐Jia; Guo, Yun‐Zhe; Hu, Wei‐Bo; Hu, Wen‐Jing; Liu, Yahu A.; Yang, Hui; Wen, Ke
Abstract: Graphyne, a theorized carbon allotrope possessing only sp‐ and sp 2 ‐hybridized carbon atoms, holds great potentials in many fields, especially in catalysis and energy‐transfer/storage devices. Using a bottom‐up strategy, we synthesized a new N‐doped graphyne analogue, triazine‐ and 1, 4‐diethynylbenzene‐based graphyne TA‐BGY, in solution in gram‐scale. The unique sp/sp 2 carbon‐conjugated TA‐BGY possesses an extended porous network structure with a BET surface area of approximately 300 m 2 g −1 . Owing to its low optical band gap (1.44 eV), TA‐BGY was expected to have many applications, which were exemplified by the photodegradation of methyl orange and photocatalytic bacterial inactivation. Abstract : Antibiosis : N‐doped graphyne analogues, triazine‐ and 1, 4‐diethynylbenzene‐based graphyne (TA‐BGY ), were synthesized through aromatic nucleophilic substitution reactions. TA‐BGY was expected to have many applications that were exampled by the photodegradation of methyl orange (99 %) and photocatalytic bacterial inactivation (see figure).